Covid-19 and the Structural Crisis of Liberal Democracies. Determinants and Consequences of the Governance of Pandemic - Alteri, Luca; Parks, Louisa; Raffini, Luca; Vitale, Tommaso (PARTECIPAZIONE E CONFLITTO, 2021)
The pandemic caused by the rapid spread of the Covid-19 virus has revealed impacts well beyond those linked to health. Indeed, it has established itself as what Mauss called a "total social fact", that is, an event that affects every single aspect of society. In this editorial we present some initial reflections on the myriad ways in which the pandemic will affect the State and the relationship between States and citizens as played out in spheres of everyday life. We begin with a brief historical overview of pandemics and the patterns, contradictions and lessons they have left, before looking at the crisis context in which the current pandemic is unfolding. We then take a look at the myriad ways in which the pandemic underlines, emphasises and exacerbates a fundamental rift in the relationship between states and citizens by discussing risk, expertise, communication, de- and re-politicisation and more. We conclude by asking ourselves if - beyond the liberal democracy vs autocracy dichotomy - the Post-Covid scenario may conduce toward a new social contract. Finally, we look to existing sociological work that might provide fruitful in moving forward to address this rift, and provide brief overviews of the contributions in this direction from the authors in this special issue.